INFLUENCE OF INTERHEMISPHERIC ASYMMETRY OF THE BRAIN ON STRUCTURAL AND FUNCTIONAL FEATURES OF AGGRESSION IN ADOLESCENTS - Stepanyan, L.S.; Tonikyan, T.G. (Modern Psychology, 2019)
Interhemispheric interactions with various manifestations of aggression were investigated. Reliable interconnections of the left frontal and behavioral components of aggression, in particular verbal and physical aggression, are shown, which allows us to consider the optimal level of aggression as a necessary quality of personality development, and not as a negative emotion. It was also revealed that indirect indicators of the degree of dominance of the right temporal cortex are closely related to the hostility factor, which is a cognitive indicator of aggression.